Redes e políticas públicas: tecendo uma perspectiva analítico-institucional - Tschiedel, Rosemarie Gartner (2006)
This thesis addresses the theme of networks, situating it in the field of Psychology as a conception that has been largely used in the formulation of public policies on mental health and on childhood and adolescence. The human being subjectivizes himself/herself having as a reference all those things and people with which they establish an association. In their turn, these become place of ties and reference where innumerable articulations and displacements occur. At the same time, however, there is a growing rupture of social ties. Also, life conditions that would guarantee dignity to the human being are becoming more and more precarious. In the same way, the State is more and more destitute of its function as a promoter of social policies that might reconduct citizenship to a status of priority. As it is, it became a goal to inquire into and analyze how the concept of networks is born and grows strong as it is perceived, on the one hand, as ontology and power and, on the other hand, and more clearly, as a term that is banalized and captured by a logic of individualism and fragmentation fabricated in neoliberalism. The focus was on how the networks become empirical and conceptual operators cartographying the images children and adolescents that children and adolescents create about their feelings of belonging to a community. Methodological procedures like focal group, elaboration of collective panels and relationship webs were used. With the contribution of Social Psychology and Institutional Analysis, which have a trajectory of political, ethical and critical positioning dialoguing with the Biology of Knowing, three images of networks were constituted to understand the interfaces of the material. The first image is that of topological webs, in the plural, identifying their interweaving. Topology is the description of a place or a portion, that may be virtual geographical and human body. The second image is of sociability webs. They represent the ties that irrupt within society; they refer to civility and to what happens among people. They have affective properties and prescind from the instruments, the language, the human being in his/her corporality, his/her history, conferring them a dimension of hybrid sociability. The third image has an analytical-institutional dimension aiming at that the analysis be produced in the web itself. They become effectively webs as they produce connections, attributing different and new meanings to this experience. This study showed that the webs are partly implemented in their topological dimensions with places and services and that the sociability webs emerge from encounters in the conversation webs, institutionalizing this movement as anti-production, that is to say, the web as a constituting power is co-opted by the logic of maintenance, reproduction and, predominantly, control. Thus, it becomes a paradigm conciliated with the time in which it emerges, where there are no investments in the processes of appropriation of collectives. However, one can work from this conception visualizing it and intervening in its processes. It is up to us to assume the need to constantly analyze introducing the analytical-institutional dimension so that each intervention potentializes autonomy and emancipation